ANALYSIS OF HAJJ REGISTRATION RESTRICTIONS POLICY (STUDY AT THE MINISTRY OF RELIGIOUS AFFAIRS OFFICE, SALATIGA CITY) - Mustadzkiroh, Mustadzkiroh; Khisni, Akhmad (Jurnal Hukum Khaira Ummah, 2023)
PMA No. 29 of 2015 on the holding of regular pilgrimage contains the minimum age requirement to register the 12-year hajj and permit to register the hajj again after 10 years from the last hajj. PMA is in response to the long queue of pilgrims, but also known as the policy of hajj restrictions , In the perspective of Law Number 13 Year 2008 normatively PMA No. 29 of 2015 is inconsistent with Law Number 13 of 2008, it can even be said to limit the right of individuals to perform worship according to their beliefs. Implementation This policy also brings positive and negative implications in society, the positive side of raising public awareness about the importance of pilgrimage and giving a sense of justice for the community to perform the pilgrimage and primarily educate the community to divert its economic potential not just hajj many times but more on quality improvement Social worship. Negative side of this provision, can be understood as a policy that castrate the right of people to carry out worship in accordance with their beliefs and cause perception in the community about the difficulty of performing the pilgrimage. The role of the Government, MUI, public figures and the Muslim community in general becomes important for the realization of the justice of society to obtain equal rights in performing the pilgrimage.Keywords: Restrictions on Hajj Registration, Individual Right of Worship, Community Justice